Knowledge and Acceptance of Human Papillomavirus Vaccine among Parents of Daughters: Bases for an Educational Program, in Al Hassa - Alqadi, Amal Ahmed; Alkadi, Maryam Ahmed; Alqadhi, Mukhtar Ahmed; Alkadi, Fatimah Ahmed (Journal of Ecohumanism, 2025)
Background: The human papillomavirus (HPV) is one of the primary risk factors for cervical cancer, a malignant neoplasm for which the HPV vaccine is available, but whose acceptance and knowledge among parents is still low in different areas, including Al Hassa, Saudi Arabia. Parental beliefs are crucial for the enhancement of vaccine acceptance and the prevention of HPV-related diseases. Aim: This study sought to assess parents’ knowledge, attitudes, health beliefs and acceptance toward HPV vaccine for their daughters in Al Hassa area. Method: A cross-sectional survey of 382 parents (mostly fathers, 67.8%) aged 40 years and oldest Saudi parents, 68.8% university educated. A structured questionnaire was used to collect information on demographics, HPV and cervical cancer knowledge, health beliefs, and vaccine decision-making attitudes. The psychometric testing of the survey scales supported their reliability. Results: Results demonstrated a lack of general knowledge, where 61.3% of parents did not have any knowledge on HPV. Public health care and media were primary information sources, with limited involvement of health professionals. Vaccination of daughters would only be accepted in 35.1 per cent of the points, because parents believed in the effectiveness of the vaccine and cancer prevention. The main barriers were lack of knowledge (56%) and stigma of the sexual transmission of HPV (37.7%). The most decision-making authority exerted over patients was by healthcare professionals (74.6%). Parents had varying views about the safety of vaccines and their incorporation in routine immunizations. Better knowledge and positive health beliefs were found to be significantly and positively associated with vaccine acceptance in the correlation analyses. Conclusion: Insufficient parental awareness and stigma are factors for low HPV vaccine acceptance in Al Hassa. Tailored educational campaigns through healthcare professionals in combination with culturally appropriate communication approaches should be used to improve vaccine coverage and to help minimize the cervical cancer burden.